2021
DOI: 10.1097/jom.0000000000002275
|View full text |Cite
|
Sign up to set email alerts
|

Prevention, Medical Management, and Adjudication of Workplace Injuries

Abstract: Objective: To describe the cost outcomes of an integrated workers’ compensation program. Methods: We studied a population that increased from 20K to 59K, incurring 8807 lost-time claims between 1988 and 2020. Results: Lost-time claims decreased from 22.15 to 4.32 per 1000 employees (1988 to 2020), and total closed lost-time claim costs per $100 payroll, decreased from $0.62 to $0.17 (1988 to 2017). The percent of claims resolved within 3 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…While some may view these costs as inevitable, there is an opportunity for CMDs to be engaged with health and safety professionals, management, and employees in efforts to both prevent workplace incidents and to manage care to expedite return to function and work. Bernacki et al 29–31 have demonstrated over a period of more than 30 years that using a combination of prevention, case management, and medical management, worker’s compensation costs could be decreased substantially. Corporate medical directors can also ensure that evidence-based guidelines are followed for injured workers, which, for example, have been shown to decrease the cost of claims for acute low back pain 32 .…”
Section: Discussionmentioning
confidence: 99%
“…While some may view these costs as inevitable, there is an opportunity for CMDs to be engaged with health and safety professionals, management, and employees in efforts to both prevent workplace incidents and to manage care to expedite return to function and work. Bernacki et al 29–31 have demonstrated over a period of more than 30 years that using a combination of prevention, case management, and medical management, worker’s compensation costs could be decreased substantially. Corporate medical directors can also ensure that evidence-based guidelines are followed for injured workers, which, for example, have been shown to decrease the cost of claims for acute low back pain 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been the experience of LWCC that claims, which close within the first 3 years, are associated with resolved disability, while older claims are associated with delayed recovery or no recovery and higher costs. In general, older age at the time of injury has been shown to be a predictor of worse outcomes 32–34 . It is not surprising that surgeries are associated with increased cost and delayed return to work because they may represent more serious injury claims, which are more likely to require hospitalization, use of analgesics, and prolonged recuperation 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, older age at the time of injury has been shown to be a predictor of worse outcomes. [32][33][34] It is not surprising that surgeries are associated with increased cost and delayed return to work because they may represent more serious injury claims, which are more likely to require hospitalization, use of analgesics, and prolonged recuperation. 12 We have shown previously that attorney involvement is also associated with adverse claims outcomes.…”
Section: Discussionmentioning
confidence: 99%